Respuesta :
[tex]\large\bold{\underline{\underline{To \: \: Differentive:-}}}[/tex]
[tex]\sf{\dfrac{a^x}{log(a)} }[/tex]
(OR)
[tex]\sf{\dfrac{a^x}{ln(a)} }[/tex]
[tex]\large\bold{\underline{\underline{Solution:-}}}[/tex]
[tex]\sf{Let\ y=\dfrac{a^x}{ln(a)} }[/tex]
[tex]\sf{=\dfrac{d}{dx}\bigg[\dfrac{a^x}{ln(a)} \bigg] }[/tex]
(Linear differentiation)
[tex]\sf{=\dfrac{1}{ln(a)}.\dfrac{d}{dx}(a^x) }[/tex]
[tex]\sf{=\dfrac{ln(a)a^x}{ln(a)} }[/tex]
[tex]\boxed{\sf{=a^x}}[/tex]
[tex]\large\bold{\underline{\underline{Applied:-}}}[/tex]
✭ Linear differentiation
→ [tex]\sf{[a.b(x)+c.d(x)]'=a.b'(x)+c.d'(x)}[/tex]
✭ Exponential function rule
→ [tex]\sf{(a^x)'=ln(a).a^x}[/tex]
Answer:
a^x.
Step-by-step explanation:
y = a^x / log a
Assuming the log is to the base e:
y = (1/ log a) * a^x
Derivative of a^x:
Let u = a^x
log u = log a^x
log u = x log a
1/u * du/dx = log a
du/dx = = u * log a
y = (1 / log a) * u
so dy/du = 1/log a
and dy/dx = dy/du * du/dx
= (1/log a )* log a u
= u
= a^x.